PRAGMATIC FEATURES OF VERB TYPES IN ENGLISH AND UZBEK LANGUAGES: ENGLISH AND UZBEK LITERARY WORKS AS EXAMPLES (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This article delves into the pragmatic characteristics of different verb types in the English language, drawing insights from renowned literary works, the intricate world of verbs in the Uzbek language, specifically focusing on their pragmatic features as showcased in Uzbek literature. By examining examples from English and Uzbek literature, this study aims to analyze how various verb types contribute to narrative depth, character development, and emotional resonance in storytelling.